The Emergence and Development of the Convergence Process of the Two Types of Standards: IFRS and US GAAP - Татьяна Николаевна Малофеева (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2016)
Tatiana Nikolaevna Malofeeva - HSE.E-mail: tmalofeeva@hse.ruIt is well known that economy is the foundation on which the state stands, and what it will be depends on the nature of economic processes in the country. One of the factors to the favorable economic climate is the creation of suitable conditions for the emergence and development of transnational corporations (TNCs). For the productive work of TNCs required standards in accordance with which the company, first, maintains its accounting records, and, secondly, provides financial statements to different users. The difficulty in this case is, on the one hand, to lead the company's activities and to provide information about the financial performance of the company in accordance with the principles of the host countries, i.e. countries in which the property is located TNCs and, on the other hand, to perform the same action only in accordance with the principles of the home country, i.e. the country in which the headquarters of TNCs. In this paper the analysis of the gradual formation and development of the process of convergence of the two types of standards: US generally accepted accounting standards (US GAAP) and international financial reporting standards (IFRS). It was found that in various periods the rate of convergence had changed considerably, caused by the change of leadership in the White House. Identified weaknesses of IFRS and justified the international community's readiness to the high speed of globalization.